Therapeutic Analysis of Smoking Cessation Efforts: Literature Review - Imam Haryoko; Chun Hoe Tan; Norhashima Abd Rashid (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: Smoking is one of the most major health problems leading to the emergence of cardiovascular disease, lung disease, and cancer in the world. Smoking cessation experiences from various backgrounds of therapy types can be input to develop successful smoking cessation strategies. Objective: This literature review is to provide comprehensive information regarding types of therapies and how support and needs are encountered to successfully quit smoking. Method: This study uses the Literature review method using PRISMA Checklist guidelines and takes electronic database data sources, namely Science direct, Google Schloar, PubMed and Perpusnas with articles published from 2013 to 2022 with the keyword smoking cessation therapy. After selection and identification according to the inclusion criteria, there were 15 articles reviewed. Results: Based on the results of an analysis of 15 research articles reviewed. There are 7 types of smoking cessation therapy including Spiritual Emotional Freedom Technique (SEFT), Cognitive Restructuring, N-Acetylcystein Mucolytic Therapy, Nicotine Replacement Therapy (NRT), Varenicline Therapy, Self-Control Therapy and Hypnoterapy. Conclusion: Smoking cessation therapy is divided into 2 parts, namely Pharmacotherapy (N- Acetylcystein Mucolytic Therapy, Nicotine Replacement Therapy (NRT), Varenicline Therapy) and Non Pharmacotherapy (Spiritual Emotional Freedom Technique (SEFT), Cognitive Restructuring, Self- Control Therapy and Hypnoterapy